2010
DOI: 10.1056/nejmoa0904485
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Acquired Rotavirus in Infants with Severe Combined Immunodeficiency

Abstract: SUMMARY Live pentavalent human–bovine reassortant rotavirus vaccine is recommended in the United States for routine immunization of infants. We describe three infants, two with failure to thrive, who had dehydration and diarrhea within 1 month after their first or second rotavirus immunization and subsequently received a diagnosis of severe combined immunodeficiency. Rotavirus was detected, by means of reverse-transcriptase–polymerase-chain-reaction (RT-PCR) assay, in stool specimens obtained from all three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(120 citation statements)
references
References 20 publications
3
110
0
7
Order By: Relevance
“…Furthermore, more intensive surveillance for evaluation of the risk of intussusceptions and for applicability to immunocompromised humans are required, since both of the 2 live oral rotavirus vaccines slightly increase the risk of intussusception and RotaTeq Ò vaccination caused vaccine-acquired rotavirus shedding or diarrhea in severe combined immunodeficient (SCID) patients. [35][36][37] Of note, evidence from licensed vaccines has suggested that parenteral vaccines can be successful in preventing orally transmitted diseases due to poliovirus, hepatitis A and B viruses, Vibrio cholera and Salmonella typhi. [38][39][40][41][42] Accordingly, the parenteral vaccines, such as subunit vaccines, could be alternative vaccine candidates for prevention of rotavirus diseases, especially in countries where rotaviruses threaten the lives of infants and young children.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more intensive surveillance for evaluation of the risk of intussusceptions and for applicability to immunocompromised humans are required, since both of the 2 live oral rotavirus vaccines slightly increase the risk of intussusception and RotaTeq Ò vaccination caused vaccine-acquired rotavirus shedding or diarrhea in severe combined immunodeficient (SCID) patients. [35][36][37] Of note, evidence from licensed vaccines has suggested that parenteral vaccines can be successful in preventing orally transmitted diseases due to poliovirus, hepatitis A and B viruses, Vibrio cholera and Salmonella typhi. [38][39][40][41][42] Accordingly, the parenteral vaccines, such as subunit vaccines, could be alternative vaccine candidates for prevention of rotavirus diseases, especially in countries where rotaviruses threaten the lives of infants and young children.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 To improve the safety and efficacy of oral rotavirus vaccines, we have pursued development of an inactivated rotavirus vaccine (IRV). 11 An IRV administered parenterally could avoid some of the problems potentially inherent with live oral vaccines -neutralization from antibodies and other antiviral substances in breast milk, transplacental antibody secreted onto the small intestine or interference from other microorganisms that diminish the efficacy of live oral vaccines.…”
Section: Does a Monovalent Inactivated Human Rotavirus Vaccine Inducementioning
confidence: 99%
“…These vaccines include the live-attenuated intranasal influenza vaccine, [38][39][40] liveattenuated rotavirus vaccine [41][42][43] and yellow fever vaccine. 44 The use of the live-attenuated influenza vaccine is not recommended in HCT recipients because of the concern for prolonged viral shedding and respiratory symptoms due to the attenuated influenza strain.…”
Section: Other Live Vaccinesmentioning
confidence: 99%
“…42 However, the use of the rotavirus vaccine in immunocompromised patients is cautioned and there are documented cases of rotavirus infections following administration of the vaccine to infants with SCID. 43 The yellow fever vaccine can cause life-threatening complications, even in healthy individuals. 44 There are case reports of successful vaccination in patients 42 years following HCT.…”
Section: Other Live Vaccinesmentioning
confidence: 99%